Saberes necessários de professores que ensinam matemática nos anos iniciais do ensino fundamental - Silva, Kely Cristina da (2023)
This study brings as a central element the knowledge of the Mathematics teachers who work in Basic Education and seeks to deepen the understanding of the importance of this knowledge for the reflection and development of teaching practice. The aim of this research is to investigate the knowledge of mathematics teachers and the relationship of this knowledge with the learning disabilities of students in the early years of elementary school in the state of Mato Grosso. The research aims to answer the following question: what is the necessary knowledge for teachers who teach mathematics in the early years of elementary school to deal with learning disabilities? As a theoretical contribution, it is initially based on the concept of the following authors: Schulman (1986, 1987), Nóvoa (1992), Schön (1992), Gonçalves and Gonçalves (1998), Gonçalves (2000), Tardif and Lessard (2009), Pimenta (2012), Tardif (2012), Gauthier (2013), Charlot (2013), Zabala (1998) and Altet (2000). It starts from the principle that the reflective professional reflects his/her action of teaching, and that this professional learning is a continuous process of knowledge and conceptions about Mathematics and its teaching-learning process, thus enabling new ways of understanding what and how to teach this discipline in the early years. As a methodological support, the research is based on the comprehensive approach, as it focuses on the study of teacher training for the analysis and reflection of the material collected from six teachers in the early years of elementary school, about their mathematical knowledge and their teaching-learning process. The instruments used in the analysis were semistructured interviews with the participants of the research and the analysis of the collected data. Using the data produced by the research, it was decided to divide them into four axes of analysis: Conception and training of teachers, Conception of mathematical knowledge, Conception of teaching practice, and Knowledge needed for good teaching practice. It points out the following results: teacher training contributes significantly to the teaching exercise, however, the participants of the research highlight that there are still gaps, so that the initial training was not able to prepare them to exercise their pedagogical practice without facing many challenges. Difficulties arise from knowledge of content, pedagogical knowledge, and in the course of the professional exercise of knowledge of experience. It concludes that for more efficient training of teachers, it is necessary to provide an opportunity in the course of the training to the knowledge that is necessary for the exercise of teaching, enabling the teacher to evaluate the way he/she develops his/her practice, and from the results pointed out, to plan changes to the weak points detected. In this sense, the research is an interesting way to stimulate discussions related to the thinking of teachers about the mathematical knowledge needed for pedagogical practice in the early years and suggests possible changes that may contribute to the training of pedagogical teachers.